2021
DOI: 10.3390/f12070903
|View full text |Cite
|
Sign up to set email alerts
|

Urban Forest Research in Malaysia: A Systematic Review

Abstract: Sustainable urban development is a major issue in developing countries, namely in environmental and social aspects. Urban forests have the potential to address these issues. Thus, it is not surprising that urban forest research is slowly gaining traction in these regions. However, there have been limited urban forest research reviews focusing on developing countries, especially tropical countries in the global south. Research reviews are vital in identifying the distribution of research themes, hence revealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This study comprehensively estimated the direct and indirect low-carbon contribution of street trees. In comparison to previous studies, which only estimated the contribution of direct carbon sequestration, this research can better reflect the role of street trees in achieving carbon neutrality [49][50][51]. In this study, taking the London plane tree as an example, it was found that the average annual carbon sequestration of this tree species was 38.9 kg, which is an approximate value of USD 7.20; however, if its comprehensive low-carbon contribution were considered, this value reached USD 18.74.…”
Section: Comprehensive Low-carbon Value Of Street Treesmentioning
confidence: 94%
“…This study comprehensively estimated the direct and indirect low-carbon contribution of street trees. In comparison to previous studies, which only estimated the contribution of direct carbon sequestration, this research can better reflect the role of street trees in achieving carbon neutrality [49][50][51]. In this study, taking the London plane tree as an example, it was found that the average annual carbon sequestration of this tree species was 38.9 kg, which is an approximate value of USD 7.20; however, if its comprehensive low-carbon contribution were considered, this value reached USD 18.74.…”
Section: Comprehensive Low-carbon Value Of Street Treesmentioning
confidence: 94%
“…The urban residents typically use the term "natural forest" more commonly than "urban forest" even though they have more experience with urban forests than natural forests outside cities. In Malaysia, the concept of the term "urban forest" is not new, but the focus has traditionally been on natural forests and forest plantations; however, the use of this term in research has been steadily increasing in recent times, indicating a growing interest in this field [20]. The rise in urban forest research can be attributed to accelerated urbanization and a growing awareness of the need for sustainable development in Malaysia.…”
Section: Natural Forests In Urban Areasmentioning
confidence: 99%
“…The increase in CO 2 in the air leads to global greenhouse and urban heat island effects, which adds to global warming [2,3]. As an essential carbon sink base, forest ecosystems can alleviate the global greenhouse effect by regulating the global carbon-oxygen balance [4][5][6]. Forests maintain the global carbon-oxygen balance through carbon release and oxygen consumption (CROC) processes and carbon sequestration and oxygen release (CSOR) processes [7,8].…”
Section: Introductionmentioning
confidence: 99%